De Internationale Vereniging voor Neerlandistiek Hoe het groeide - Grave, Jaap (Lage Landen Studies, 2022)
Dutch is an important language, not only in Europe. Beyond Flanders and the Netherlands, there are 200 universities and colleges worldwide where over 15.000 students study Dutch as a language, investigate the language or are being educated to become an interpreter or a translator. Right now, the greatest Dutch university departments are not even situated in the Netherlands or in Flanders. Those departments represent the Dutch culture abroad. For over fifty years the International Association for Dutch studies (IVN) has been serving the interests of international Dutch scholars who educate students, do research, give lectures, make dictionaries, write literary histories and organize congresses. This book describes the exciting history of IVN.